PENGGUNAAN DAUN KELOR (Moringa oleifera) UNTUK PENGOBATAN DIABETES - Yohandini, Heni; Fitrya, Fitrya; Elfita, Elfita; Maryadi, Maryadi; Muharni, Muharni (Jurnal Pepadu, 2024)
Diabetes is a disease that is often found in society. Various treatment methods are offered for healing, ranging from medical treatment to non-medical treatment using herbal medicines. Various complications can occur due to diabetes, including decreased kidney function, nerve damage, blindness, and even amputation. Considering the dangers of diabetes, the use of Moringa leaves has been introduced to the community in Indralaya Mulya Village to lower blood sugar levels. The step of activity include education on the use of Moringa leaves to lower blood sugar levels, introduction to various dosage forms of Moringa leaves and checking the blood sugar levels of participants. The results of this activity show that people tend to understand diabetes and the impacts it causes, so they have a great desire to avoid diabetes. People are know various traditional medicinal plants, especially Moringa oleifera leaves and various dosage forms that can be used to maintain blood sugar levels. The results of checking blood sugar levels showed that of the 20 participants examined, only one person had blood sugar levels above normal. Based on these activities, it was concluded that the people of Indralaya Mulya have a great desire to maintain health by using medicinal plants.